MATHEMATICS ANXIETY AND ITS EFFECTS ON ENGINEERING STUDENTS’ PERFORMANCE DURING THE COVID 19 PANDEMIC - Derling Jose Mendoza Velazco; Elizeth Mayrene Flores Hinostroza; Magda Francisca Cejas Martínez; Edith Josefina Liccione (Journal on Mathematics Education, 2021)
The research objective was to describe the levels of anxiety and their effects on performance manifested by the mathematics students of the engineering faculty of the National University of Chimborazo UNACH during the 2020-1 academic semester. The study is in the quantitative paradigm with a descriptive exploratory design. The total sample consisted of 120 students studying mathematics, which are at different levels and careers of the engineering faculty. The sample selection was of an intentional non-probabilistic type and had as inclusion criteria not having been diagnosed with an anxiety disorder. The Brief Anxiety Situations and Responses Inventory was applied (ASRI-B). The ASRI-B was sent to students by email to facilitate data collection. The two-factor ANOVA (mathematics and comprehension) uses to analyze the research results. It's allowed to find statistically significant differences in the grasp of the contents presented by the teachers in a virtual way for the cognitive and physiological response system and the general level of anxiety, as well as in situational areas of evaluation anxiety and anxiety in everyday situations, during the academic closure in the quarantine season due to the COVID-19 pandemic.